1982
DOI: 10.1038/ki.1982.95
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of vitamin D-dependent calcium-binding protein in renal tubules of rabbit, rat, and chick

Abstract: Vitamin D-dependent calcium-binding protein (CaBP) was localized in tissue sections of kidneys from rabbits, rats, and chicks using antiserum specific for chick intestinal CaBP. In rabbit kidney, CaBP was present in all cells of the distal convoluted tubule and most cells of the connecting tubule. Fewer, but still a majority, of the cells of cortical collecting ducts contained CaBP. The intensity of immunochemical staining and the number of stained cells decreased markedly in medullary collecting ducts, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 24 publications
6
68
0
Order By: Relevance
“…The functional reasons for this difference remain obscure. Constitutive expression throughout the embryonic collecting duct tree is quite different from the cortically restricted, 1,25(0H),D3-dependent pattern reported in the adult (Taylor et al, 1982;Rhoten and Christakos, 1981;Roth et al, 1982). It is, however, analogous to the constitutive expression in the drainage channel of embryonic mesonephros, the Wolffian duct.…”
Section: Discussionmentioning
confidence: 60%
“…The functional reasons for this difference remain obscure. Constitutive expression throughout the embryonic collecting duct tree is quite different from the cortically restricted, 1,25(0H),D3-dependent pattern reported in the adult (Taylor et al, 1982;Rhoten and Christakos, 1981;Roth et al, 1982). It is, however, analogous to the constitutive expression in the drainage channel of embryonic mesonephros, the Wolffian duct.…”
Section: Discussionmentioning
confidence: 60%
“…To define the distribution of the OS-3-immunoreactive cells, double immunostaining with calbindin and cytokeratin antisera was performed. In the distal convoluted tubule, all epithelial cells were stained positively by the calbindin antiserum as reported previously (TAYLOR et al, 1982), whereas no cells in this region were immunoreactive with OS-3. In the connecting segment, about two-thirds of the epithelial cells were immunoreactive for calbindin and intermingled with OS-3-immunoreactive cells (Fig.…”
Section: Immunohistochemistry With Os-3 Monoclonal Antibodysupporting
confidence: 48%
“…Immunohistochemistry for calbindin has labeled almost all epithelial cells in the distal convoluted tubule and also scattered cells in the connecting segment, as previously reported (TAYLOR et al, 1982). Thus, calbindin is regarded as a marker for the distal convoluted tubule and ontogenetically related cells in the connecting segment.…”
Section: Discussion Os-3-immunoreacitve Cells Are Type B Intercalatedmentioning
confidence: 58%
“…Taylor et al [34], using sections of rabbit kidney, have demonstrated that most cells of CNT and initial portion of the CCD contain calbindin-Dm , which is generally accepted to be indicative of the occurrence of transcellular Ca2* transport. Similar ly, we have demonstrated that the majority («80%) of the cultured cells is calbindin-D28k positive, whereas the re mainder is peanut-lectin positive and, therefore, recog nized as intercalated cells [22,35].…”
Section: Discussionmentioning
confidence: 99%